Exposure of Inpatients to Antibacterials at the José de Mello Saúde Hospital Units: Exposição dos Doentes Internados nas Unidades José de Mello Saúde a Antibacterianos - Freitas, Ana; Plácido, Ana; Vinagre, Ana; Ferrer, Carla; Cardoso, Joana; Guerra, Joana; Marques, Joana; Branco, José; Pereira, Maria; Almeida, Pedro; Oliveira, Rita; Barroso, Sara; et al. (Gazeta Médica, 2017)
INTRODUCTION: The rational use of antibacterials is a critical factor in controlling the emergence of antimicrobial resistance, and represents a global public health issue. Thus, José de Mello Saúde considered it relevant and developed a retrospective study about antibacterials utilization in the years 2014 and 2015 by a comparative analysis of the use of antimicrobials intra and interunits, setting as the main goal the rational use of antimicrobials and the optimization of prevention and control of infections policies in the different hospital units of José de Mello Saúde. MATERIALS AND METHODS: Antibacterial utilization was analysed by ATC (anatomical therapeutic chemical) code expressed in daily defined dose (DDD) per 100 beds per day was analyzed in six Hospital Units: CUF Infante Santo, CUF Descobertas, CUF Cascais, CUF Porto, Hospital de Vila Franca de Xira and Hospital de Braga. DISCUSSION: During the study period, there was an increase in the overall use of antibacterials and a preponderant utilization of antibacterials by parenteral route, which demonstrates the need to implement policies that can promote the rational use of this class of drugs, as well as the standardization of good practices and the use of antibacterials use and or prescription protocols across all units.